Genotoxic Effects of the Essential Oil Obtained from Satureja hortensis Against to Hordeum Vulgare L. Seedlings - Bozari, Sedat; Cakmak, Birsen; Kurt, Havva (KAHRAMANMARAS SUTCU IMAM UNIV, 2017)
Plants use in many fields has increased significantly with the increasing of biotechnological methods from past to present. Their secondary metabolites are commonly used in many fields from medicine to agriculture. Because of their easy degradation, they will be used as an alternative to the synthetic chemicals. Deciding their proper non-phytotoxic doses for cereals will secure their safe usage. The present study aimed to determine the potential biopesticide activity of plants natural components in weeds. Thus, the essential oils obtained from Satureja hortensis species of Lamiaceae family were subjected to analysis of volatiles and applied to Hordeum vulgare L. seedlings. Potential genotoxic effects of these components on the seedlings were determined by RAPD (Randomly Amplified Polymorphic DNA) PCR. The oils were applied in four different doses (0.2, 0.4, 0.8 and 1.6 mu L mL(-)(1)). Results indicated that the third (0.4 mu L mL(-)(1)) dose has changed the genomic stability about 46.16 % and remaining doses changed the genomic stability over the 50 %. The effects of the essential oils on root and stem length of barley seedlings were varied. The oils have increased the root length and inhibited stem length in all doses compared to the control. It was concluded that plant essential oil components showed similar effects of synthetic chemicals in the literature. With the exception of the 0.4 mu L mL(-)(1), which may be phytotoxic in Hordeum vulgare L. seeds, all doses tested in the study have the potential to be used as bio pesticides against weeds.
Keywords: Biopesticide; Allelopathy; Essential Oils; GTS